2016
DOI: 10.21829/abm114.2016.1103
|View full text |Cite
|
Sign up to set email alerts
|

Pollen profile of propolis produced on the eastern edge of the Sonoran Desert in central Sonora, Mexico

Abstract: Eight propolis samples from the eastern edge of the Sonoran Desert were collected at two sites (Pueblo de Álamos and Rancho Viejo, located at Ures, Sonora, Mexico) during two seasons of the year (winter and summer, 2012 and 2013) and analyzed using palynological methods in order to determine which plants were visited by bees in order to collect raw material (resins, wax and pollen) to form propolis. The pollen analysis identified a total of 42 pollen types. Six samples of propolis were bifloral (summer and win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…Los propóleos en greña estudiados presentaron tonalidades en marrón verdoso con tintes amarillos, parámetro que no puede estandarizarse por ser dependiente del origen vegetal. El aroma en su mayoría fue balsámico, que se relaciona con compuestos aromáticos y volátiles de mezclas complejas entre alcoholes, aldehídos, cetonas y ésteres o terpenos, estos últimos presentes en especies de la familia Pinaceae La variación en la vegetación presente en cada localidad hace que sea importante utilizar métodos palinológicos con el fin de determinar qué flora fue visitada por las abejas para recolectar la materia prima (resina, cera y polen) para formar los propóleos (Ramírez-Arriaga et al, 2016;Vargas-Sánchez, Peñalba-Garmendia, Sánchez-Escalante, Torrescano-Urrutia & Sánchez-Escalante, 2016).…”
Section: S Aureusunclassified
“…Los propóleos en greña estudiados presentaron tonalidades en marrón verdoso con tintes amarillos, parámetro que no puede estandarizarse por ser dependiente del origen vegetal. El aroma en su mayoría fue balsámico, que se relaciona con compuestos aromáticos y volátiles de mezclas complejas entre alcoholes, aldehídos, cetonas y ésteres o terpenos, estos últimos presentes en especies de la familia Pinaceae La variación en la vegetación presente en cada localidad hace que sea importante utilizar métodos palinológicos con el fin de determinar qué flora fue visitada por las abejas para recolectar la materia prima (resina, cera y polen) para formar los propóleos (Ramírez-Arriaga et al, 2016;Vargas-Sánchez, Peñalba-Garmendia, Sánchez-Escalante, Torrescano-Urrutia & Sánchez-Escalante, 2016).…”
Section: S Aureusunclassified
“…Propolis samples were collected from the Sonoran Desert, central Sonora, during two seasons of the year (S, summer; W, winter; 2017). The location presents desert climate characteristics, and the sampling site is surrounded by foothills or thorn-scrub, dominated by Fabaceae, Cactaceae, Malvaceae, and Asteraceae families (Vargas-Sánchez et al, 2016). In each season, propolis samples were collected from two collection locations: 1, Pueblo of Alamos (29°8'51.36" N, 110°7'26" W; 636 m a.s.l.…”
Section: Propolis Collectionmentioning
confidence: 99%
“…Data obtained on the proximate composition of the collected propolis samples (Table 1) revealed PS1 and PS2 samples had the lowest moisture content (P<0.05), which can be related to the weather conditions (temperature and humidity) during the collection (Vargas-Sánchez et al, 2016). In the current study, propolis samples collected during winter showed the highest (P<0.05) contents of ash and mechanical impurities (10.3 and 20.8%, respectively), which can be explained by the presence of vegetal material (leaves and woods) in the samples, insect remains, and soil, among others (NOM, 2017).…”
Section: Physicochemical and Microbial Counts Of Propolis Samplesmentioning
confidence: 99%
“…The word of "Propolis" comes from Greek is "Pro" means "in defence of" and "Polis" means "city". Propolis uses by honeybees (Apis mellifera L.) for protecting the honeybees from microbial infections and diseases, protecting the hive from any external invaders and extreme environmental conditions, providing the hygienic situations in hives, making smaller the entrance pore of hives, repairing the hives and the usage of propolis in folk medicine dates ancient times (Vargas-Sánchez et al 2016;Silici 2019). Besides propolis is used for food preservatives because of its natural protector features in food industry (Bahtiti 2010;Günhan et al 2022).…”
Section: Introductionmentioning
confidence: 99%